Legal psychology as a science in the field of law. (Journal of actual problems of jurisprudence, 2016)
This is article covers historical aspects which are the reason establishment of jurist psychology as a separate science of law. Questions arising in relation to this subject have been given answers psychologists,lawyers and other scientists branches of law. Primary stage the emergence and development jurist psychology due to the necessity of psychological knowledge. In the article discusses in a wide order history jurist psychology and reflected the names of high-profile woks of scientists in this sphere. Also described the base of emergence judicial psychology and psychiatry which are basic and inseparable parts of jurist psychology.
Keywords: psychology; psychiatry; criminology; reflexology